AN ASSESSMENT OF SHAREHOLDERS PROFITABILITY AS A STRATEGY FOR TAX AVOIDANCE. - Chesoli, Joshua (IJRDO - Journal of Business Management, 2023)
Tax avoidance is a common problem among many nations all over the world, especially the developing and third world countries. Most citizens see tax payment as very offensive, and seek all means to avoid tax liabilities. Kenya is not exempted from this economic menace. In spite of the several tax holidays enjoyed by firms in Kenya, most firms have resorted to creatively avoid tax under the disguise of shareholders wealth maximization. This act is seen by the researchers as a corporate governance factor because the provision of bonus schemes by shareholders for managers for abnormal wealth maximization had justified the act of tax avoidance in the Kenyan corporate world.